2023
DOI: 10.3390/nano13111754
|View full text |Cite
|
Sign up to set email alerts
|

Features of Copper and Gold Nanoparticle Translocation in Petroselinum crispum Segments

Abstract: The application of metal nanoparticles in industry and medicine results in their release into the environment, which can have a negative impact on human health. The effects of gold (AuNPs) and copper (CuNPs) nanoparticles at the concentration range of 1–200 mg/L on parsley (Petroselinum crispum) under conditions of root exposure and their translocation in roots and leaves were investigated in a 10-day experiment. The content of copper and gold in soil and plant segments was determined using ICP-OES and ICP-MS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
2
2
0
Order By: Relevance
“…Previously, Malejko et al [ 34 ] showed that AuNPs were accumulated in roots, stems, and leaves of potato plants, with a much higher concentration remaining in the soil. The same finding was reported by [ 35 ].…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Previously, Malejko et al [ 34 ] showed that AuNPs were accumulated in roots, stems, and leaves of potato plants, with a much higher concentration remaining in the soil. The same finding was reported by [ 35 ].…”
Section: Resultssupporting
confidence: 91%
“…Previously, Malejko et al [34] showed that AuNPs were accumulated in roots, stems, and leaves of potato plants, with a much higher concentration remaining in the soil. The same finding was reported by [35]. Mentha spicata L. treatment via spraying did not influence gold content in soil at AuNPs concentrations of 1-10 mg/L.…”
Section: Gold Content In Soil and Nanoparticles' Effect On Soil Micro...supporting
confidence: 89%
See 2 more Smart Citations